2019
DOI: 10.1002/jemt.23197
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different ratios of nano‐sized hydroxyapatite fillers on the micro‐tensile bond strength of an adhesive resin

Abstract: The purpose of this study was to evaluate the micro‐tensile bond strength (μTBS) of dentin bonding agents containing different ratios of nano‐sized hydroxyapatite fillers (HA). X‐ray diffraction analysis was used for characterization, and scanning electron microscope (SEM) analysis was used to determine the HA particle size after that HA were mixed a bonding agents without filler. Dentin bonding agents were divided into four groups according to addition of different ratios of nano‐sized hydroxyapatite fillers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Particularly they could serve as nuclei in excess demineralized dentin regions lacking the HA crystal nuclei. Thus, demineralized zones in hybrid layer region could be remineralized [83].…”
Section: Methods To Modify the Bonding Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly they could serve as nuclei in excess demineralized dentin regions lacking the HA crystal nuclei. Thus, demineralized zones in hybrid layer region could be remineralized [83].…”
Section: Methods To Modify the Bonding Systemmentioning
confidence: 99%
“…Bioactive glass (BAG), calcium phosphate (CaP), and HA could potentially be used as a source of CaP and as an adjunct to biomimetic remineralization, allow epitaxial deposition of CaP on their external surfaces [83]. The endogenous MMPs fossilized by the growth of apatite mineral, consequently protecting collagen fibrils [85].…”
Section: Methods To Modify the Bonding Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As the dental adhesives come in direct contact with the tooth dentin, incorporation of HA nano particles in resin adhesives can possibly remineralize the caries affected dentin. In addition, interaction of HA within the hybrid dentin layer forming an organic bond, will contribute positively to its bond strength to tooth [19]. In an earlier study, Leitune et al reported that inclusion of nano-HA particles in the experimental adhesive improved its bond strength to dentin [20].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism remineralizes the demineralized regions within the hybrid layer to increase the long-term stability of DAs [ 39 ]. Kavrik reported that MBN induces biomimetic remineralization as a source of CaP [ 55 ]. The DA-MBN and DA-MBN-Zn utilized in this study release Ca 2+ and PO 4 3− and may induce biomimetic remineralization ( Figure S3 and Table S2 ).…”
Section: Discussionmentioning
confidence: 99%